Fitness value based evolution algorithm approach for text steganalysis model - Din, Roshidi; Samsudin, Azman; Tuan Muda, Tuan Zalizam; Lertkrai, P.; Amphawan, Angela; Omar, Mohd Nizam (Seventh Sense Research Group, 2013)
In this paper, we present a new alternative method for text steganalysis based on an evolution algorithm, implemented using the Java Evolution Algorithms Package (JEAP).The main objective of this paper is to detect the existence of hidden messages ased on fitness values of a text description.It is found that the detection performance has been influenced by two groups of fitness values which are good fitness value and bad fitness value. This paper provides a valuable insight into the development and enhancement of the text steganalysis domain.